Early Life Environments and Frailty in Old Age among Chinese Older Adults - Yaxi Li; Qian-Li Xue; Michelle C. Odden; Xi Chen; Chenkai Wu (Global Labor Organization (GLO), 2020)
Exposures in childhood and adolescence may impact the development of diseases and symptoms in late life. However, evidence from low- and middle- income countries is scarce. In this study, we examined the association of early life risk factors with frailty among older adults using a large, nationally representative cohort of community-dwelling Chinese sample. 6,806 participants aged ≥60 years from the China Health and Retirement Longitudinal Study were included. We measured 13 risk factors in childhood or adolescence through self-reports, encompassing six dimensions (education, family economic status, nutritional status, domestic violence, neighborhood, and health). We used multinomial regression models to examine the association between risk factors and frailty and further calculated the absolute risk difference for the statistically significant factors. Results show that worse health condition in childhood and unfavorable childhood and adolescent socioeconomic status as measured by educational attainment and neighborhood quality may increase the risk of late-life frailty among Chinese older adults. Severe starvation in childhood was associated with higher risk of prefrailty. The risk differences of being frail were 5.7% lower for persons with a high school or above education, 1.5% lower for those whose fathers were literate, 4.8% lower for the highest neighborhood quality, and 2.9% higher for worse childhood health status compared to their counterparts.
Keywords: I10; I14; I18; 330; Early Life Environments; Life Course Health; Physical Health; Frailty; Aging; China